Randomised trial of home sleep apnoea testing compared to in-lab polysomnography for the evaluation of obstructive sleep apnoea in children: rationale and study protocol - Darko Stefanovski; Ignacio E Tapia; Christopher M Cielo; Lourdes M DelRosso; Eberechukwu A Uwah; Yaelis D Roman Rosado; Mahalakshmi Somayaji; Michelle Ward; Anjalee Galion; Sally L Davidson Ward (BMJ Open, 2025)
Introduction Obstructive sleep apnoea (OSA) affects 1–5% of the paediatric population, including 55–90% of children with Down syndrome (DS), and has been associated with negative effects on neurocognitive development, cardiovascular health, immune development and quality of life. In-lab attended polysomnography (PSG) is currently the gold standard for the diagnosis of OSA in children, but it poses challenges due to the burden on families and limited testing facilities. Home sleep apnoea testing (HSAT), an unattended sleep test done at home, is an accepted alternative for adults but lacks sufficient evidence to be used clinically for the evaluation of OSA in children. HSAT may be especially beneficial for children with DS or others with sensory issues or those who struggle with sleeping in a laboratory setting overnight.Methods and analysis This single-centre trial compares HSAT to PSG for the diagnosis of OSA in children, including those with DS. The trial will enrol 317 children 5–12 years old, including approximately 100 with DS. The primary outcome is the diagnostic accuracy of HSAT compared with PSG for OSA evaluated through ROC. Secondary outcomes include the agreement between HSAT and PSG for therapeutic decision-making and comparison of preference and acceptability of HSAT versus PSG. This trial seeks to evaluate HSAT as an alternative diagnostic tool for paediatric OSA, potentially expanding testing options for clinicians and families.Ethics and dissemination This study has been approved by the Institutional Review Board at Children’s Hospital of Philadelphia (#21–0 19 533). Informed consent will be obtained from all participants, and no identifiable data will be reported.Trial registration number NCT05382754.